ALD of TiO2/ZnO mutilayers towards the understanding of optical properties and polarizability. (August 2021) - Fouad, S.S.; Parditka, B.; Bekheet, A.E.; Atyia, H.E.; Erdélyi, Z.
Highlights: A comparative study of multilayers of TiO2 /ZnO thin films, grown by atomic layer deposition. The dispersion of the refractive index was discussed in terms of the ( WDD ) model. The absorption coefficient and skin depth were studied as a function of the number of layers. Some of the dielectric parameters have been studied base on (n) data. Electronic polarizability and reflection loss factor have been determined. Abstract: In this research we report a comparative study of multilayers of TiO2 /ZnO thin films, grown on glass and silicon substrates by atomic layer deposition (ALD) at 100 °C. All prepared multilayers are nominally 100 nm thick with a varying number of alternating TiO2 /ZnO layers. The obtained data from X-ray diffraction pattern suggest that layer growth does not influence the structure of the films and all the films were completely amorphous. Optical studies including the measurement of the spectral dependence of reflection and transmissions were used to calculate the refractive index (n) and extinction coefficient (k). On the basis of n data, the dielectric constant (ɛr ), optical dielectric constant (σopt ), dielectric susceptibility (χ), electronic polarizability (αe ), reflection loss factor (RL ) and transmission coefficient (TC ) were obtained. The dispersion of the refractive index was discussed in terms of the Wemple – DiDomenico (WDD) model. The relationship between linear (n0 ) and nonlinear (n2 ) refractive indices has been examined on the basis of the (WDD) parameters. The metallization criteria (Rm /Vm and M) were also obtained. The absorption coefficient (α), optical density (OD), skin depth (ϕ) and optical conductivity (δ) were studied as a function of the number of layers in thin-film samples. It was established that the band gap energy (Eg ) decreases with the increasing number of layers. The relationship between the non-linear refractive index and optical energy gap was investigated through their own parameters. We claim that the change in the above-mentioned parameters are closely associated with (/related to) the change of the bilayer thickness of the thin TiO2 /ZnO films.